1993
DOI: 10.3109/01460869309078272
|View full text |Cite
|
Sign up to set email alerts
|

The use of Photography to Explore the Meaning of Health Among Adolescents with Cancer

Abstract: The purpose of this exploratory-descriptive pilot study was to explore the use of photography to examine the meaning of health among adolescents who have been diagnosed with cancer. The sample consisted of 4 adolescents who had been diagnosed with cancer and were attending a weekend retreat. Participants were given Polaroid cameras with instructions to take pictures that illustrated health. The participants were then interviewed to obtain an understanding of how their pictures demonstrated health. The particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 10 publications
1
33
0
2
Order By: Relevance
“…Les méthodes de narration visuelle ont été peu utilisées jusqu'à présent en recherche clinique. Chez l'enfant et l'adolescent, elles ont été utilisées pour décrire le vécu de la maladie chronique, de l'expérience du cancer ou du diabète (DREW & AL 2010, HANNA & AL 1993, BUCHBINDER & AL 2005. A notre connaissance, la photo-elicitation a été utilisée pour la première fois dans la recherche en psychiatrie au sein du groupe QUALIGRAMH pour explorer le rôle de la nourriture dans les relations familiales …”
Section: Faculté De Médecine Deunclassified
“…Les méthodes de narration visuelle ont été peu utilisées jusqu'à présent en recherche clinique. Chez l'enfant et l'adolescent, elles ont été utilisées pour décrire le vécu de la maladie chronique, de l'expérience du cancer ou du diabète (DREW & AL 2010, HANNA & AL 1993, BUCHBINDER & AL 2005. A notre connaissance, la photo-elicitation a été utilisée pour la première fois dans la recherche en psychiatrie au sein du groupe QUALIGRAMH pour explorer le rôle de la nourriture dans les relations familiales …”
Section: Faculté De Médecine Deunclassified
“…Another study used photography as way of exploring the meaning of health among adolescents with cancer (Hanna & Jacobs, 1993). The authors asked four adolescents diagnosed with cancer to write a description of health, and take photographs representing health.…”
Section: The Visual Metaphormentioning
confidence: 99%
“…However, as discussed in Section 4.2, one study has used photography to explore the meaning of health among adolescents diagnosed with cancer (Hanna & Jacobs, 1993). It was observed that photography facilitated otherwise inhibited communication between adults and adolescent clients, and the task was deemed enjoyable by the adolescents.…”
Section: 2a Photography As a Therapeutic Toolmentioning
confidence: 99%
“…O uso da fotografia na pesquisa, como recurso à comunicação, tem sido utilizado em estudos fenomenológicos na área da saúde para estimular a discussão sobre experiências de difícil abordagem para a vida dos pacientes (Hanna & Jacobs, 1993). A idéia de utilizar a fotografia como uma mediação para a comunicação foi desenvolvida por Collier & Collier (1986), no livro Visual antropology: photography as a research method.…”
Section: A Pesquisa: Procedimentos Metodológicosunclassified